Integrated Microcantilever for Joint Thermal Analysis of Trace Hazardous Materials - Yuhang Yang; Xinyu Li; Zechun Li; Ming Li; Ying Chen; Shaokui Tan; Haitao Yu; Pengcheng Xu; Xinxin Li (Sensors)
During the thermal analysis of hazardous materials, the thermal instruments available may face the risk of contamination within heating chambers or damage to the instruments themselves. Herein, this work introduces an innovative detection technology that combines thermogravimetric and differential thermal analysis with an integrated MEMS cantilever. Integrating polysilicon thermocouples and a heat-driven resistor into a single resonant cantilever achieves remarkable precision with a mass resolution of 5.5 picograms and a temperature resolution of 0.0082 °C. Validated through the thermal analysis of nylon 6, the cantilever excels in detecting nanogram-level samples, making it ideal for analyzing hazardous materials like ammonium perchlorate and TNT. Notably, it has successfully observed the evaporation of TNT in an air atmosphere. The integrated MEMS cantilever detection chip offers a groundbreaking micro-quantification solution for hazardous material analysis, significantly enhancing safety and opening new avenues for application.